Latin American aquatic mammals: An overview of 12 years focusing on molecular techniques applied to conservation - Loizaga de Castro, Rocio (2023)
Ecological information useful for conservation purposes have benefitted from recent and rapid advancements in genetic techniques, revealing unknown aspects of behavior, natural history, population structure and demography of several aquatic mammal species, many of them with conservation concerns. Molecular markers have been used to define management units, to settle taxonomic uncertainties, to control illegal wildlife trade, among others, providing valuable information to decision-making to conserve and manage aquatic mammals. We review genetic studies applied to conservation-related issues involving natural populations of more than 40 species of aquatic mammals in Latin America, covering four taxonomic groups. The main goal was to assess which genetic approaches have been used and to identify gaps in genetic research relating to geographic areas and species. We reviewed studies published in peer-reviewed journals between 2011 and 2022, and found that most were focused on population structure, phylogeography, gene flow and dispersal movements. The review revealed that researchers need to increase and improve the knowledge in those species which face major conservation concern. Scarce findings were related to forensics and its application to wildlife trade. In the era of next-generation-sequencing techniques, just a few studies used genomics as a tool for monitoring gene diversity, an important goal to help us predict how species will cope with climate change events. Looking to the future we suggest which species, geographic areas and genetic studies should be prioritized in a scenario of climate change and increased human threats (e.g., fishery bycatch, habitat degradation, etc.) and the urgent need for conservation actions. Finally, we highlight the benefits of the collaborative works and the necessity of generating a conservation genetic network, with an open agenda to discuss the local and regional problematics. All in all, we strongly emphasize the generation of critical information towards the effective conservation and management of aquatic mammals in Latin America.